Trends and Collaborative Networks in Reflective Intelligent Surface (RIS)-Enhanced Free Space Optics (FSO): A Bibliometric Analysis (ELEKTRIKA- Journal of Electrical Engineering, 2024)
This bibliometric analysis investigates research trends and collaborative networks in the emerging field of Reflective Intelligent Surface (RIS)-Enhanced Free Space Optics (FSO) to understand its growth and impact. With the rising complexity of modern wireless communication systems, RIS-enhanced FSO has gained attention for its potential to address challenges related to signal quality, energy efficiency, and resilience in diverse environments. Despite this potential, gaps remain in understanding collaboration patterns, influential contributions, and key research themes. Using Scopus Analyzer and VOSviewer software, a dataset of 1,449 publications was analysed to identify major contributors, popular keywords, and global collaboration trends. The methodology involved mapping co-authorship networks and keyword co-occurrences, enabling a detailed examination of prominent research areas and key geographical hubs. The results show a steady increase in publication volume from 2017 onward, indicating heightened research interest, particularly between 2022 and 2023. Popular keywords such as "signal to noise ratio," "bit error rate," and "atmospheric turbulence" highlight the focus on enhancing communication reliability and mitigating environmental impacts on FSO systems. Key contributors and collaborations were identified, with notable influence from researchers and institutions across multiple countries, underscoring the field’s interdisciplinary and global nature. This study concludes that RIS-enhanced FSO research is primarily driven by engineering and computational disciplines, with increasing attention to practical applications. The expanding collaborative network reflects a collective effort to overcome technical challenges and optimize RIS applications for future communication needs, establishing RIS-enhanced FSO as a vital area for next-generation wireless innovation.
Keywords: RIS; FSO; trends; bibliometric